The valuation of pedagogical objects by the method of comparison - Mališauskienė , A.; Stakvilevičius , M. (Psichologija, 1972)
A mathematical apparatus is offered. By its help it is possible to define ranks of a group of pedagogical objects if references of different experts about distribution of places in sub - groups are known. With the help of this method the distribution of academic groups in the institute and of classes in the school according to the progressiveness was defined. This method can be used for defining places of classes, teachers, schools and other pedagogical objects taking into account the opinion of experts.